Revealing patterns of the effective mechanical characteristics of cellular sheet polycarbonate for explosion venting panels - Pozdieiev, Serhii; Myhalenko, Kostiantyn; Nuianzin, Vitalii; Zemlianskyi, Oleh; Kostenko, Tetiana (Eastern-European Journal of Enterprise Technologies, 2020)
Explosive concentrations of various substances can accumulate inside industrial premises. In the presence of a sufficient amount of oxygen and an ignition source, such a situation could lead to explosion that may result in the destruction of building structures and the building in general. Strengthening the stability of supporting structures is aimed at protecting industrial premises against possible destruction by explosion indoors. One of the effective ways to protect construction structures against the excessive pressure of explosion is to use explosion venting panels. In order to solve practical tasks on protecting industrial premises and structures against explosion, one must be able to choose both the area and parameters for explosion venting panels. In addition, in order to reduce the related loads to safe quantities, it is necessary to properly calculate the bearing structures in terms of dynamic stability while maintaining their carrying capacity. The set task to ensure protection against explosion by applying explosion venting panels with flexible elements can be solved through integrated accounting for mechanical properties of cellular polycarbonate sheets. We have performed experimental research into performance of the inertia-free explosion venting panels with flexible enclosing elements exposed to dynamic loads under conditions of explosion. Based on the obtained results, the effective rigidity and critical displacement of cellular polycarbonate sheets of flexible elements have been determined. It has been established that for cellular polycarbonate sheets with a thickness of 4‒8 mm effective rigidity ranges within 301–215 N·m; the critical displacement of edges in this case is 2.9–9.8 mm. A mathematical model has been proposed that takes into consideration the influence of geometric dimensions and the critical value of deflection in a polycarbonate sheet as the flexible element of fencing on the operational conditions for explosion venting panels